Problematika Surat Perintah Penghentian Penyidikan (SP3) Oleh Komisi Pemberantasan Korupsi (KPK) Dalam Tindak Pidana Korupsi di Tinjau Dari Perspektif Keadilan Berdasarkan Pasal 40 Ayat 1 Undang – Undang Komisi Pemberantasan Tindak Pidana Korupsi - Subekhi, Mohamad; Jopie Gunawan; Yudha Koswara, Indra; Jopie Gunawan, Tanumihardja (UNES Law Review, 2024)
This research discusses the issue of the issuance of an Order to Terminate Investigation (SP3) by the Corruption Eradication Commission (KPK) in corruption cases. The main focus lies on the effect of the application of Article 40 paragraph (1) of the KPK Law which authorizes SP3, as well as its impact on justice and legal integrity. On the one hand, the SP3 authority is considered to provide legal certainty for suspects, but on the other hand, it triggers concerns regarding the potential for abuse of authority and negotiation practices that harm substantive justice. This research uses a normative legal approach by analyzing laws and regulations and court decisions. The results show that the issuance of SP3 by the KPK has the potential to harm the principle of justice, especially in corruption cases involving officials with broad access to power. Therefore, it is important to ensure that the application of SP3 authority is carried out carefully and transparently so as not to damage the integrity of the legal system and public trust.